Les musiciens et la musique - Berlioz, Hector 1803-1869; Hallays, André (Paris Calmann-Lévy, 1903)
Mozart/Don Juan - Cherubini - Lesueur - Meyerbeer/Les Hugenots, Le Prophète - Herold/Zampa - Donizetti/La fille du Régiment- Halévy/Le Val d'Andorre - Bellini - Adam/Le Torréador - Glinka - David/Le Désert - Thomas/Le Caïs - Gounod/Sapho, Faust - Litolff - Offenbach/Barkouf - Reyer/La Statue - Bizet/Pêcheurs de perles
Keywords: 19th Century (1801-1900); Music criticism; Opera; France